Pengaruh keputusan investasi, struktur modal, profitabilitas, dan kebijakan dividen terhadap nilai perusahaan - Dewi, Luh Gede Nirvana (Entrepreneurship Bisnis Manajemen Akuntansi (E-BISMA), 2021)
The existence of research aims to find out how the company's value occurred in the basic industry and chemical subsector pulp & paper in 2014-2018. In increasing the value of the company, a manager is very influential on decisions taken including investment decisions, dividend policies and funding decisions, every decision taken affects financial decisions. Some factors that affect the value of the company are capital structure, dividend policy, company growth, liquidity, company size and investment decisions. Type of research is quantitative using financial data listed on financial statements listed on the IDX (Indonesia Stock Exchange). Investment decisions are the allocation of capital into investment proposals should be evaluated and linked to the risks and results expected to obtain a high level of return with a certain level of risk. Dividend policy is a decision on whether the profit earned will be divided as dividends or will be withheld as an upcoming investment. The Company may be distributed to shareholders as dividends or withheld in the form of retained earnings to finance the company's investments. The capital structure is the balance of the amount of short-term debt that is permanent, long-term debt, preferred shares and common shares, capital structure decisions. Profitability is revenue minus expenses and losses during the reporting period. Analysis of profitability is critical for creditors and equity investors.